A study of the Malaysian educational system with recommendations for the introduction of social studies in the schools - Aziz, Zahara Binti Abdul ([Quezon City s.n.], 1974)
The purpose of this paper is to point out the inadequacies of the present Malaysian education system in reference to the national education goals and objectives. Much of the educational problem besetting the present Malaysian system had their root causes during the British colonial administration. Furthermore, this study shows the inadequacies of the present education system viewed from the perspective of the school curriculum organization.
Thesis (M.A.T.Social Studies)--University of the Philippines.
Keywords: Education -- Malaysia; Social sciences--Study and teaching -- Malaysia